Susceptibility to calcium dysregulation during brain aging - Kumar, Ashok; Bodhinathan, Karthik; Foster, Thomas C. (Frontiers in Aging Neuroscience, 2009)
Calcium (Ca2+) is a highly versatile intracellular signaling molecule that is essential for regulating a variety of cellular and physiological processes ranging from fertilization to programmed cell death. Research has provided ample evidence that brain aging is associated with altered Ca2+ homeostasis. Much of the work has focused on the hippocampus, a brain region critically involved in learning and memory, which is particularly susceptible to dysfunction during senescence. The current review takes a broader perspective, assessing age-related changes in Ca2+ sources, Ca2+ sequestration, and Ca2+ binding proteins throughout the nervous system. The nature of altered Ca2+ homeostasis is cell specific and may represent a deficit or a compensatory mechanism, producing complex patterns of impaired cellular function. Incorporating the knowledge of the complexity of age-related alterations in Ca2+ homeostasis will positively shape the development of highly effective therapeutics to treat brain disorders.